Tanggung Jawab Hukum Rumah Sakit Terhadap Pasien Akibat Salah Sisi Operasi - Ristyani Krisnawati (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Hospitals have an obligation to provide services in accordance with standard operating procedures for patient care, maintain patient safety and security, and provide accurate information. Incorrect medical treatment such as surgery on the side of the body that is not in accordance with the diagnosis can have a serious impact on the patient. The wrong side of the operation on the patient caused by the negligence of medical staff may result in legal liability for negligence. The hospital can be held responsible and obliged to provide compensation for the physical, emotional and financial losses suffered by the patient. If an incident occurs that harms the patient, the hospital may be subject to lawsuits. Hospitals must be legally responsible and take steps to improve the medical service system to improve quality and patient safety.